Cortico-limbic morphology separates tinnitus from tinnitus distress - Leaver, Amber M.; Seydell-Greenwald, Anna; Turesky, Ted; Morgan, Susan; Kim, Hung J.; Rauschecker, Josef P. (Frontiers in Systems Neuroscience, 2012)
Tinnitus is a common auditory disorder characterized by a chronic ringing or buzzing “in the ear.”Despite the auditory-perceptual nature of this disorder, a growing number of studies have reported neuroanatomical differences in tinnitus patients outside the auditory-perceptual system. Some have used this evidence to characterize chronic tinnitus as dysregulation of the auditory system, either resulting from inefficient inhibitory control or through the formation of aversive associations with tinnitus. It remains unclear, however, whether these “non-auditory” anatomical markers of tinnitus are related to the tinnitus signal itself, or merely to negative emotional reactions to tinnitus (i.e., tinnitus distress). In the current study, we used anatomical MRI to identify neural markers of tinnitus, and measured their relationship to a variety of tinnitus characteristics and other factors often linked to tinnitus, such as hearing loss, depression, anxiety, and noise sensitivity. In a new cohort of participants, we confirmed that people with chronic tinnitus exhibit reduced gray matter in ventromedial prefrontal cortex (vmPFC) compared to controls matched for age and hearing loss. This effect was driven by reduced cortical surface area, and was not related to tinnitus distress, symptoms of depression or anxiety, noise sensitivity, or other factors. Instead, tinnitus distress was positively correlated with cortical thickness in the anterior insula in tinnitus patients, while symptoms of anxiety and depression were negatively correlated with cortical thickness in subcallosal anterior cingulate cortex (scACC) across all groups. Tinnitus patients also exhibited increased gyrification of dorsomedial prefrontal cortex (dmPFC), which was more severe in those patients with constant (vs. intermittent) tinnitus awareness. Our data suggest that the neural systems associated with chronic tinnitus are different from those involved in aversive or distressed reactions to tinnitus.